ANALISIS HABITS OF MIND MATEMATIS SISWA SMP DI KOTA TANGERANG - Safitri, Prahesti Tirta (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
This research is motivated by the ability of Habits of mind that is very supportive of the learner's appearance in everyday life. Habits of mind is the root of the students' strength in exercising their ability to determine solutions in a problems. Classroom is a condition or environment they occupy as they study. Therefore, teachers really should be able to see the habits of the student's mind when the learning process occurs and teachers have a minimal important role to remind students of the importance of the habits of mind, so they are helped in completing various tasks, especially in mathematics. Habits of mind (HOM) is a tendency to behave intellectually or intelligently when faced with problems, especially problems that are not immediately known to the solution. HOM there are 16 indicators and in this study the researchers gave a HOM questionnaire to 78 students with the results of research that there are 13 students included in the high category, 56 students who are in the medium category and 9 students in the low category.